An in-depth investigation on the grain growth and the formation of secondary phases of ultrasonic-sprayed Cu2ZnSnS4 based thin films assisted by Na crystallization catalyst. (December 2018) - Kermadi, S.; Sali, S.; Zougar, L.; Boumaour, M.; Gunder, R.; Schorr, S.; Izquierdo-Roca, V.; Pérez-Rodríguez, A.
Highlights: In-depth study of sodium (Na) assisted grain growth in sprayed Cu2 ZnSnS4 based thin films. A strong impact of Na content on morphology and crystallinity was observed. The Kesterite PS-CZTS formation with traces of Cu2 S, ZnS and ZnO secondary compounds was confirmed. Uniform Na diffusion throughout the films was observed with grain size enhancement up to 2 µm. The developed process showed a promising potential for the formation of high quality PS-CZTS films. Abstract: Up to date, the absorber low grain growth and the secondary compound formation remain the main factors causing the poor performance of kesterite solar cells based on spray pyrolysis derived Cu2 ZnSnS4 (pure sulfide CZTS = PS-CZTS) compared with other deposition techniques. As the sodium (Na) inclusion is known to play a crucial role in affecting the grain growth, we evaluated in this report a thorough investigation in depth of the effect of Na doping content on crystallinity and phase segregation. The PS-CZTS was deposited by ultrasonic spray pyrolysis while the Na incorporation was carried out by soaking the pre-heated sprayed films in a solution of an environmentally-friendly NaCl salt. The change in the investigated parameters was followed throughout the absorber by scanning electron microscopy, Raman spectroscopy with different excitation wavelengths, grazing incidence X-ray diffraction (GIXRD) with various incidence angles, energy dispersive X-ray spectroscopy (EDS), secondary ion mass spectrometry (SIMS) and UV–Vis spectrometry. Increasing Na content significantly improves the crystallinity and the compactness simultaneously, resulting in smoothest surfaces with grains up to 2 µm in size. The Na was uniformly diffused leading to similar grain growth throughout the films. Whatever the Na content, the deposited materials are mostly consisting of ketserite-type PS-CZTS, whereas the use of different Raman excitations reveal the presence of Cu2 S, ZnS and ZnO as secondary compounds in trace forms. The depth profile analysis with GIXRD showed that no further phase segregation has occurred while the EDS and SIMS results showed uniform distribution of PS-CZTS′ constituents along the surface and within the deposited films. By combining Raman, GIXRD and EDS analysis, the secondary compounds were found to be mostly gathered in the upper absorber layer. The absorption coefficient and the band gap range around 10 4  cm −1 and 1.55 eV respectively, the optimal values required for photovoltaic energy conversion. The Na doping developed in this study has a promising potential to yield high quality sprayed absorbers and opens up access to opportunities in enhancing of sprayed PS-CZTS thin film solar cell performances.